Exercise‐induced lung cancer regression: Mechanistic findings from a mouse model. Issue 21 (2nd July 2014) - Higgins, Kristin A.; Park, Dongkyoo; Lee, Gee Young; Curran, Walter J.; Deng, Xingming
Abstract : BACKGROUND: It has been demonstrated that regular exercise improves the quality of life in patients undergoing treatment for lung cancer and has been associated with reductions in cancer‐specific mortality in patients with colon and breast cancer. The direct effects of cardiovascular exercise on lung cancer tumor biology, however, remain unknown. The authors evaluated the effects of cardiovascular exercise in a mouse model of lung adenocarcinoma. METHODS: Luciferase‐tagged A549 lung adenocarcinoma cells were injected through the tail vein of nude male mice. Then, the mice underwent weekly bioluminescent imaging until lung tumors were clearly identified. After lung tumors were identified, the mice were randomized to daily wheel running versus no wheel running, and they were imaged weekly. After 4 weeks, all mice were killed, and the lung tumors were harvested. Western blot and immunohistochemical analyses were conducted on tumor tissues to identify potential differences in protein expression levels in exercising mice versus sedentary mice. RESULTS: Lung tumors in exercising mice grew significantly more slowly relative to sedentary mice. There was no change in the development of metastatic lesions between the 2 groups. Protein analysis by Western blot or immunohistochemical analysis demonstrated increased p53 protein levels in exercising mice relative to sedentary mice as well as increased mediators of apoptosis, including Bax and active caspase 3, in tumor tissues. In both groups of mice, no normal tissue toxicity was observed in other organs. CONCLUSIONS: Daily cardiovascular exercise appears to mitigate the growth of lung adenocarcinoma tumors, possibly by activation of the p53 tumor suppressor function and increased apoptosis. Cancer 2014;120:3302–3310. © 2014 American Cancer Society . Abstract : This study demonstrates that daily cardiovascular exercise reduces lung tumor growth in mice, and tumor apoptosis is increased. Exercise should therefore be further explored as a potential anti‐cancer therapy.